2020
DOI: 10.3390/polym12102344
|View full text |Cite
|
Sign up to set email alerts
|

Core-Shell Nanofibers of Polyvinylidene Fluoride-based Nanocomposites as Piezoelectric Nanogenerators

Abstract: Flexible piezoelectric nanogenerators (PENG) are widely applied to harvest sustainable energy from multiple energy sources. The rational and simple design of PENG have great potential in soft electronics. Here we design a highly flexible PENG using the polyvinylidene fluoride (PVDF) and its copolymer, polyvinylidene hexafluoropropylene (PVDF-HFP) with two nanoarchitectures of semiconducting metal oxides, TiO2 and ZnO. The nanotubes of TiO2 and nanoflowers of ZnO are embedded in these different polymeric media … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Compared with other methods, electrospinning, which can be broadly divided into solution electrospinning and melt electrospinning, is commonly considered to be one of the most economically and technically efficient approaches to obtain ultrafine fibers [ 5 , 10 ]. Solution electrospinning was developed rapidly from a single-fluid blending processes [ 11 ] to coaxial [ 12 ], side by side [ 13 ], tri-axial [ 14 ], and other complex processes [ 15 ]; however, the high toxicity of organic solvent used in the solution electrospinning for preparation of working fluid is incompatible with the in vivo biomedical applications [ 16 ]. Thus, besides convenience and simplicity, energy saving [ 17 ] and environmental friendliness [ 18 ] are always desired for developing new electrospinning processes.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other methods, electrospinning, which can be broadly divided into solution electrospinning and melt electrospinning, is commonly considered to be one of the most economically and technically efficient approaches to obtain ultrafine fibers [ 5 , 10 ]. Solution electrospinning was developed rapidly from a single-fluid blending processes [ 11 ] to coaxial [ 12 ], side by side [ 13 ], tri-axial [ 14 ], and other complex processes [ 15 ]; however, the high toxicity of organic solvent used in the solution electrospinning for preparation of working fluid is incompatible with the in vivo biomedical applications [ 16 ]. Thus, besides convenience and simplicity, energy saving [ 17 ] and environmental friendliness [ 18 ] are always desired for developing new electrospinning processes.…”
Section: Introductionmentioning
confidence: 99%
“…Electrospinning is one of the simple and effective fabrication methods for producing fibrillar structures made from a variety of biopolymers whose diameter can be formed from a nano to micro-scale. During the past several decades, electrospinning has progressed from single-fluid blending processes [9,10] to coaxial [11,12], tri-axial [13,14], side-by-side [15,16], and other complicated processes [17]. On the other hand, it is also combined with more and more traditional physical and chemical methods to expand its potential applications in the applied scientific fields [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The SiO 2 @P(VDF-HFP) nanofibrous membranes also formed a superhydrophilic surface with a contact angle near to 0◦. Ponnamma et al [ 11 ] designed a highly flexible piezoelectric nanogenerator (PENG) using PVDF and P(VDF-HFP) composite nanofibers filled with two nanostructured semiconducting metal oxides: nanotubes of TiO 2 and nanoflowers of ZnO. The research showed that the composite nanofiber mats, with excellent mechanical strength, ligh weight and flexibility, are capable of producing a good output voltage (a maximum of 14 V) during different mechanical vibrations at various frequencies and in response to human motion.…”
Section: Introductionmentioning
confidence: 99%